2017
DOI: 10.1088/1741-4326/aa7f91
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-drivenm  =  2 island formation and dynamics near density limit in experimental advanced superconducting tokamak ohmic plasma

Abstract: A radiation-driven m = 2 island was observed in the experimental advanced superconducting tokamak (EAST) ohmic plasma, near the density limit. The mode onset occurs when the the ohmic heating input is less than the radiative cooling loss, which agrees with the mode onset behavior of the thermo-resistive model. The evolution of the equilibrium during the mode process was obtained using the ONETWO transport code, with inputs comprising the experimental electron temperature and density profiles. A large m = 2 isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…8, as suggested by previous studies. [18] Figure 9 shows that the reconstructed signals match well with the measured signals.…”
Section: Sawtooth-like Internal Disruptionmentioning
confidence: 60%
“…8, as suggested by previous studies. [18] Figure 9 shows that the reconstructed signals match well with the measured signals.…”
Section: Sawtooth-like Internal Disruptionmentioning
confidence: 60%
“…Experiments have found some correlations between the impurity radiation and the tearing mode (TM) growth, ASDEX-Upgrade shows the low temperature and localized impurity radiation inside the growing magnetic island during the current contraction phase [1], and the similar connection between enhanced radiation and enlarged island width is observed in NSTX [2]. Besides, EAST experiments demonstrate the m = 2 (m is the poloidal mode number) island formation when the radiative cooling exceeds the ohmic heating [3]. Those experimental observation contribute to supporting the impurity radiation as a driven mechanism of TM but without more detail, JET experiments show the TM onset induced by unstable shrinking (broadening) current profile as a consequence of temperature edge cooling (central hollowing) from radiation loss [4].…”
Section: Introductionmentioning
confidence: 86%
“…The impurity level is sufficiently low to avoid triggering the fast major disruption such as in a massive gas injection (MGI) process [15], while sufficiently high to excite the resistive tearing modes as in recent EAST experiments [11]. The impurity penetrates inward mainly through diffusion and convection as governed by equation (3). A constant isotropic diffusion coefficient D = 10m 2 /s is adopted in the simulation, which is larger than the typical EAST experimental value, i.e.…”
Section: Nimrod/kprad Model and Simulation Setupmentioning
confidence: 99%
“…Such studies on plasma radiation have been carried out, including bremsstrahlung, recombination radiation, cyclotron radiation and line radiation. [16,[26][27][28][29][30][31][32][33][34] It is worth mentioning that the line radiation comes mainly from the impurity radiation in the tokamak plasmas. Gates et al found that islands could be driven by the plasma radiation and this performance was consistent with the density limit.…”
Section: Introductionmentioning
confidence: 99%
“…[29] An m = 2 island induced by the plasma radiation was explored in EAST ap-proaching to the density limit when the loss of plasma radiation is more than the ohmic heating input. [30] Besides, Hu et al numerically studied plasma radiation response and MHD destabilization by a 3D-code JOREK and observed that the mode growth was propelled by the current, leading to the collapse in core temperature. [31] Furthermore, Salzedas et al advanced a new theory that MHD instabilities could be induced by plasma radiation.…”
Section: Introductionmentioning
confidence: 99%